Analysis of Intensity Distribution in the He-Ne Laser Beam by Gaussian Distribution Function - N. Abd, Ahmed; Jawad Alwan, Bahaa; M Abdulridha, Wasna’a (International Journal of Engineering and Technology, 2018)
The purpose of this research is to analyze the distribution of density in the laser beam, both from the experimental and theoretical point of view. I measured the density distribution through the He-Ne laser beam and prepared an attempt to compare it with the Gaussian distribution function. Image profiling can be used to determine the distance of objects depending on the distribution of the laser beam spot surroundings by their width. It can also be used to take pictures of things and define their distances and shape things. As we see, Nubia is very good. From the compatibility analysis found that (the program that made the fitting mention of GNUPLOT).Â